Teaching adult ESOL Principles and practice - Paton, Anne; Wilkins, Mery (New York, USA McGraw-Hill, 2009)
This is one of the few books to effectively blend together research, theory and practical pedagogy and link this directly with the context of teaching English to adults. There are reflective tasks throughout, which encourage you to develop and apply your theoretical knowledge to your own experiences
"Developing adult skills"
"National research and Development center for adults literacy and numeracy"
12
Keywords: English as a second language; English language -- Study and teaching; English language -- Usage; Language and languages; Language arts